(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Theproject’sgoalistoassesshowwell,twowell-known machine learning algorithms, multiple linear regression, and XGBoost Regressor, estimate the price of a house. To implement this concept, a dataset of past real estate transactions was gathered, and key features such as the property’s location, size, number of bedrooms and bathrooms, and additional amenities wereidentifiedforanalysis